Sociologists in Love, Sociology as Passion - MIHAI CERNEA (Revista Română de Sociologie, 2013)
In Sociologists in Love, Sociology as Passion, Michael Cernea reacts to the correspondence between Anton Golopenţia and Ştefania Cristescu published in Rapsodia epistolară (Rhapsody in Letters), vol. II as a passionate reader and a sociologist. He thus warmly and esentially concludes the initial triptych in which each of the authors felt the need to address not only St.C. the sociologist, but also the person.